Adsorption of acetone and isopropanol on organic acid modified activated carbons. Issue 2 (June 2016) - Tang, Lin; Li, Liqing; Chen, Ruofei; Wang, Chunhao; Ma, Weiwu; Ma, Xiancheng
Abstract: Commercial activated carbon (AC) was modified using formic acid, oxalic acid, and sulfamic acid separately. The effects of the modification on the physicochemical properties of ACs were evaluated using specific surface area and pore distribution, scanning electron microscope, and Fourier transform infrared spectroscopy. After the modification, (i) the BET specific surface area and total pore volume of ACs decreased, (ii) uneven etching trace and white crystal particles were observed on the surface of AC, and (iii) more oxygen-containing functional groups such as OH, CO, CO, and SO were formed on the surface. The effects of the modifications on the adsorption behavior of acetone and isopropanol on ACs at different inlet concentrations were studied from adsorption equilibrium, kinetics, and energy point of view. The results show that the equilibrium adsorption capacity has been greatly improved by the modification of organic acids. The adsorption isotherms of acetone and isopropanol on ACs are well fitted by both Langmuir and Freundlich equations. Characteristic adsorption energy values of acetone and isopropanol slightly increase with increasing of oxygen functional groups on the ACs surface. The adsorption kinetics of acetone and isopropanol on ACs are best described by Bangham kinetics model.